Pengaruh Customer Relationship Marketing dan Customer Value Terhadap Customer Loyalty - Zuhdi, Saefudin; Syarif, Rini; SEC, Gempita Santi (Jurnal Ilmiah Manajemen Kesatuan, 2015)
The purpose of this study was to determine how much influence the Customer Relationship Marketing and Customer Value on Customer Loyalty. The author conducted research at PT. Bank Central Asia, Tbk Graha Cibinong Branch Ofice, located at Jalan Raya Bogor Km 46 Graha D6-D7. Data collection is done by distributing questionnaires to 100 respondents BCA customers Graha Cibinong, taken at random. The data processing method using validity, reliability, and classical assumptions. While the method of data analysis used is by using multiple linear regression analysis, and test hypotheses derived from data collected from questionnaires filled out and processed. The survey results revealed that the Customer Relationship Marketing and Customer Value has a positive and significant influence. Keywords: Customer Relationship Marketing, Customer Value, Customer Loyalty